Magneto-Mechanical Actuators with Reversible Stretching and Torsional Actuation Capabilities. (13th February 2019) - Razzaq, M. Yasar; Behl, M.; Lendlein, A.
ABSTRACT: Composite actuators consisting of magnetic nanoparticles dispersed in a crystallizable multiphase polymer system can be remotely controlled by alternating magnetic fields (AMF). These actuators contain spatially segregated crystalline domains with chemically different compositions. Here, the crystalline domain associated to low melting transition range is responsible for actuation while the crystalline domain associated to the higher melting transition range determines the geometry of the shape change. This paper reports magneto-mechanical actuators which are based on a single crystalline domain of oligo(ω-pentadecalactone) (OPDL) along with covalently integrated iron(III) oxide nanoparticles (ioNPs). Different geometrical modes of actuation such as a reversible change in length or twisting were implemented by a magneto-mechanical programming procedure. For an individual actuation mode, the degree of actuation could be tailored by variation of the magnetic field strengths. This material design can be easily extended to other composites containing other magnetic nanoparticles, e.g. with a high magnetic susceptibility.